Analysis of Reality Construction Theory on Social Media Coverage of the Revision of Broadcasting Bill 2024 - Dri Fia Yulanda; Aliyudin Sofyan; Zulfatan Faizin Abdulkarim (Social Impact Journal, 2024)
This article about the analysis of reality construction theory on the news of the revision of the 2024 broadcasting bill aims to explain and provide new thoughts on the suitability between the concept of reality construction and the news of the revision of the broadcasting bill in the digital era. How the function and role of the media in overseeing the process of the bill, so as to achieve goals to a wider public audience. Because social media has been widely used by the public to access all information on social media. The writing method uses a qualitative method that focuses on the theory of reality construction on the news of the broadcasting bill draft. The result of this research is that there is a news construction that is not just an objective report about a fact, but is the result of a social construction process.